109 Hyponatraemia in Older Patients is Often Untreated, Despite Greater Mortality Burden; Results of A Prospective Cohort Study. (6th February 2020) - Thorpe, O; Cuesta, M; Tormey, W T; Sherlock, M; Williams, D J; Thompson, C J; Garrahy, A
Abstract: Introduction: Hyponatraemia is associated with increased morbidity and mortality, and is commoner in elderly patients. The aetiology and outcomes of hyponatraemia in the elderly has not been defined in prospective studies. Methods: A single-centre 9 month prospective observational study of hyponatraemic (HN) patients (</= 130 mmol/L) was performed. Clinical outcomes in patients ≥65 years (Elderly patients, EP) and those <65 years (Young Patients, YP) were analysed, and compared with age-matched eunatremic controls, Analysis was performed using Graphpad-Prism 7. Results: 1321 consecutive admissions with hyponatraemia (67% EP, median age of EP 77 (65–98) years) and 1122 eunatremic controls (63% EP, median age of EP 77 (65–99) years) were analysed. Median nadir plasma sodium was similar in both groups with HN, 128 (107–130) mmol/L EP vs 128(110–130) mmol/L YP (p = 0.62). EP hyponatraemic patients were more likely to have hypovolaemic hyponatraemia (34%) compared with YP with hyponatraemia (28%, p = 0.03). Diuretic-induced hyponatraemia was twice as common in EP (8%) compared with YP (4%, p = 0.01). Malignancy-induced SIAD occurred with similar frequency in both groups (7% in EP SIAD vs 8% in YP SIAD, p = 0.65). Respiratory disease was causative in 10% cases of EP SIAD, compared with 4% in YP SIAD, p = 0.0004. Hyponatraemia was corrected in 53% of EP, compared with 64% of YP, p = 0.0001. Length of stay and re-admissions rates were similar across hyponatraemia age groups. EP with HN were 2.4 times more likely to die in hospital, compared with eunatremic age-matched controls, (OR 2.4, 95% CI 1.6–3.7, p < 0.0001). Conclusions: The causation of hyponatraemia is different in elderly patients. Hyponatraemia in EP is often uncorrected, despite increased mortality compared with eunatremic age-matched controls.